Kalibrasi Sensor Monitoring Cuaca pada Area Lokal untuk Meningkatkan Akurasi pada Sensor Biaya Rendah - Sugeng, Sugeng; Nizar, Taufiq Nuzwir; Jatmiko, Didit Andri; Hartono, Rodi; Kerlooza, Yusrila Yeka (Komputika : Jurnal Sistem Komputer, 2024)
Current weather monitoring data can be accessed in real-time through applications on Android and desktop devices provided by BMKG. Data sensors installed in specific areas or through monitoring in a particular region. BMKG sensors installed only in a limited number of areas, this study aims to evaluate and improve the accuracy of sensors used in weather monitoring systems in tropical regions. Sensor calibration is conducted using standard methods along with special adjustments for local conditions. Each sensor is tested under conditions that represent the actual environmental conditions, alongside a reference sensor for calibration. The calibration process involves collecting data from the lowest range of sensor readings to a certain range according to the sensor's or testing equipment's capabilities. The sensor readings are then compared with those of the reference measuring devices, and linear regression analysis is performed to examine the distribution of the sensor data against the actual sensor data. The calibration results yield equations that can be used to adjust the sensors to align with the actual sensors. All sensors are then installed and tested for several days to assess the calibration results. The study findings indicate an improvement in accuracy after calibration and provide recommendations for field use